Do age‐specific survival patterns of wild boar fit current evolutionary theories of senescence?. (1st December 2014) - Gamelon, Marlène; Focardi, Stefano; Gaillard, Jean‐Michel; Gimenez, Olivier; Bonenfant, Christophe; Franzetti, Barbara; Choquet, Rémi; Ronchi, Francesca; Baubet, Eric; Lemaître, Jean‐François
Abstract: Actuarial senescence is widespread in age‐structured populations. In growing populations, the progressive decline of Hamiltonian forces of selection with age leads to decreasing survival. As actuarial senescence is overcompensated by a high fertility, actuarial senescence should be more intense in species with high reproductive effort, a theoretical prediction that has not been yet explicitly tested across species. Wild boar ( Sus scrofa ) females have an unusual life‐history strategy among large mammals by associating both early and high reproductive effort with potentially long lifespan. Therefore, wild boar females should show stronger actuarial senescence than similar‐sized related mammals. Moreover, being polygynous and much larger than females, males should display higher senescence rates than females. Using a long‐term monitoring (18 years) of a wild boar population, we tested these predictions. We provided clear evidence of actuarial senescence in both sexes. Wild boar females had earlier but not stronger actuarial senescence than similar‐sized ungulates. Both sexes displayed similar senescence rates. Our study indicates that the timing of senescence, not the rate, is associated with the magnitude of fertility in ungulates. This demonstrates the importance of including the timing of senescence in addition to its rate to understand variation in senescence patterns in wild populations.